2020
DOI: 10.3390/ijerph17041167
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of An Educational Intervention of Breast Cancer Screening Practices Uptake, Knowledge, and Beliefs among Yemeni Female School Teachers in Klang Valley, Malaysia: A Study Protocol for a Cluster-Randomized Controlled Trial

Abstract: Breast cancer is the most common cancer spread among women worldwide. Whereas many studies have discussed the significance of breast cancer screening among women in various countries, few have attempted to discuss this topic among female school teachers. As teachers educate and communicate with students, this may play an essential role in health education and in promoting healthy behavior, such as breast cancer screening. The primary goal of this study is to develop and implement an educational intervention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…The educational intervention on the breast cancer screening practice uptake, knowledge, and health beliefs of Yemeni female school teachers in Klang Valley, Malaysia using a randomized control trial study was proven to be effective and successful [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The educational intervention on the breast cancer screening practice uptake, knowledge, and health beliefs of Yemeni female school teachers in Klang Valley, Malaysia using a randomized control trial study was proven to be effective and successful [7].…”
Section: Discussionmentioning
confidence: 99%
“…These improvements can be attributed to the content of the program, which covered all the identified needs and knowledge gaps among the students. Likewise, an educational intervention on breast cancer screening practice uptake, knowledge, and health beliefs among Yemeni female school teachers in Klang Valley, Malaysia was proven to be effective in a randomized controlled trial [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…After analysing the data, it can be said that the level of awareness in individuals who participated in the studies contained in the research shown increased significantly [43] as a result of the various educational interventions on BC, particularly in aspects concerning new information and early detection methods. This indicates that the educational interventions are effective, managing to significantly increase the level of awareness in all their variants, leading to future quality of life through timely detection, linked with prevention and control of the disease and with improvements in life styles [33,37,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the importance of preventive BC health education interventions, in all stages of life, is reiterated, in order to develop health-promoting behaviours that allow the detection and timely control of risks in the development of BC. Its effectiveness has been demonstrated, but the need to have the knowledge, skills and competencies necessary to be able to transmit relevant and updated education on the subject is highlighted [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Yemen, as a developing country, is a case in point, with a low rate of BCS practice among its women, ranging between 11 and 17.4% [ 6 , 7 ], therefore resulting in a higher probability for a later stage of identification of most BC cases [ 8 ]. Influenced by their status as foreign immigrants, Yemeni women in Malaysia are significantly impacted by the challenges and barriers in accessing BCS-related information and services available for Malaysian women, thus resulting in the low level of BCS uptake among this ethnic group [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%